Pharmacokinetics and metabolism of Chf197, a ligustrazine derivative, in rats. (3rd August 2015) - Li, Wenlong; Liu, Huiqing; Wei, Chunmin; Wei, Xinbing; Tang, Mingtan; Kong, Xianglin; Chen, Hongfei; Liu, Xinyong; Guo, Ruichen
Abstract: Ligustrazine is the most abundant and bioactive ingredient in Rhizoma Chuanxiong, a Chinese medicinal herb commonly used for the treatment of cardiovascular diseases. Chf197 is one of the structurally modified ligustrazine derivatives in a purpose of overcoming the rapid metabolism and short half‐life of original. The plasma and urine pharmacokinetics of Chf197 in rats were studied after intravenous or intraperitoneal injection of Chf197 with the validated RP‐HPLC method. The pharmacokinetic parameters of Chf197 injected intravenously 20 mg/kg were as follows: Cmax, 1.44 ± 0.4 mg/L; Tmax, 0.08 h; t 1/2, 3.03 ± 1.67 h; AUC, 3.85 ± 3.88 h/L; Vd, 31.66 ± 11.79L/kg; and CL, 9.29 ± 4.92 l/h/kg. Dose‐dependent pharmacokinetics was observed, and a significantly higher dose‐normalized AUC after intravenous administration was obtained than that after intraperitoneal administration. A possible metabolite was detected at about 3.1 min, and full‐scan mass spectrum was adopted to predict its possible structure.